Konsep Pemimpin dalam Tafsir Al-Qur'ānul Karīm Karya Abdul Halim Hasan, Abdurrahim Haitami, Zainal Arifin Abbas: The Concept of Leader in Tafsir Al-Qur'ānul Karīm by Abdul Halim Hasan, Abdurrahim Haitami, Zainal Arifin Abbas - Arif, Zuhri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
The aim of this study is to analyze the concept of the leader in the interpretation of al-Qur'ānul karīm by Abdul Halim Hasan, Abdurrahin Haitami and Zainal Arifin Abbas. The method used in this research is library research with a qualitative descriptive research type. The results of this study indicate that there is no significant prohibition against electing women leaders, but in this case Abdul Halim Hasan, Abdurrahin Haitami and Zainal Arifin Abbas, do not recommend electing women leaders when there are still men participating in the election process. In fact, women are people in life, while choosing non-Muslim leaders, this is clearly forbidden, and there are no exceptions to this.